Reliability and utility of citizen science reef monitoring data collected by Reef Check Australia, 2002–2015. Issue 1 (15th April 2017) - Done, Terence; Roelfsema, Chris; Harvey, Andrew; Schuller, Laura; Hill, Jocelyn; Schläppy, Marie-Lise; Lea, Alexandra; Bauer-Civiello, Anne; Loder, Jennifer
Abstract: Reef Check Australia (RCA) has collected data on benthic composition and cover at > 70 sites along > 1000 km of Australia's Queensland coast from 2002 to 2015. This paper quantifies the accuracy, precision and power of RCA benthic composition data, to guide its application and interpretation. A simulation study established that the inherent accuracy of the Reef Check point sampling protocol is high (<± 7% error absolute), in the range of estimates of benthic cover from 1% to 50%. A field study at three reef sites indicated that, despite minor observer- and deployment-related biases, the protocol does reliably document moderate ecological changes in coral communities. The error analyses were then used to guide the interpretation of inter-annual variability and long term trends at three study sites in RCA's major 2002–2015 data series for the Queensland coast. Highlights: Reef Check Australia conducts a major coral reef monitoring program in Queensland. Inherent accuracy of the monitoring protocol used is high (<± 7% error). Ecologically important changes are detectable because measurement biases are low.